Crystallization and preliminary X-ray crystallographic studies of CrArsM, an arsenic(III) S-adenosylmethionine methyltransferase from Chlamydomonas reinhardtii - Packianathan, Charles (International Union of Crystallography, 2014)

(untitled)
Arsenic is one the most toxic environmental substances. Arsenic is ubiquitous in water, soil and food, and ranks first on the Environmental Protection Agency’s Superfund Priority List of Hazardous Substances. Arsenic(III) S-adenosylmethionine methyltransferases (AS3MT in animals and ArsM in microbes) are key enzymes of arsenic biotransformation, catalyzing the methylation of inorganic arsenite to give methyl, dimethyl and trimethyl products. Arsenic methyltransferases are found in members of every kingdom from bacteria to humans (EC 2.1.1.137). In the human liver, hAS3MT converts inorganic arsenic into more toxic and carcinogenic forms. CrArsM, an ortholog of hAS3MT from the eukaryotic green alga Chlamydomonas reinhardtii, was purified by chemically synthesizing the gene and expressing it in Escherichia coli. Synthetic purified CrArsM was crystallized in an unliganded form. Crystals were obtained by the hanging-drop vapor-diffusion method. The crystals belonged to space group R3:H, with unit-cell parameters a = b = 157.8, c = 95.4 Å, γ = 120° and two molecules in the asymmetric unit. Complete data sets were collected and processed to a resolution of 2.40 Å.